2020
DOI: 10.3390/su12062171
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Channel Return Policy in a Green Dual-Channel Supply Chain Considering Spillover Effect

Abstract: With the advent of the era of “New Retail”, many manufacturers and retailers have begun to provide cross-channel return services to increase competitiveness. Our study takes return policy into a green dual-channel supply chain, wherein a manufacturer creates and sells green products simultaneously. We investigate the pricing and greening strategies for the supply chain players in the cases of providing and not providing cross-channel return service by employing the Stackelberg model under the hypothesis of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…To verify the correctness of the above models and propositions, this section uses MATLAB software for numerical simulation and model analysis. In the case of meeting the assumptions of the model in this paper, we refer to the assignment ideas in the literature [60][61][62]. Table 3 shows the initial values of the parameters and the source paper.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…To verify the correctness of the above models and propositions, this section uses MATLAB software for numerical simulation and model analysis. In the case of meeting the assumptions of the model in this paper, we refer to the assignment ideas in the literature [60][61][62]. Table 3 shows the initial values of the parameters and the source paper.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Based Equation (7),and ( 15), the GDCSC model in the model (a) is obtained, max Π 𝑎 (𝑃 𝑚 , 𝑃 𝑟 , 𝑥) = Π 𝑚 𝑎 + Π 𝑟. 𝑎 (17) Then in the model (b), the GDCSC model in the decentralization scenario can be constructed by using Equation ( 9) and ( 16), thus obtaining max Π 𝑏 (𝑃 𝑚 , 𝑃 𝑟 , 𝑥) = Π 𝑚 𝑏 + Π 𝑟 𝑏 . (18) In this section, the GDCSC model has been obtained in model (a) and model (b) using the centralized scenario. Next, the optimal solution for each model obtained is determined.…”
Section: Retailer Profit Amountmentioning
confidence: 99%
“…An application is given by performing numerical simulations on a green dual-channel supply chain model considering product returns and remanufacturing processes. The parameter values are taken from the research of Chang et al [17] and Zhang et al [18], and numerical simulations. The parameter values used in this study are presented in Table 2.…”
Section: Applicationmentioning
confidence: 99%
“…Regarding dual-channel, Zhang et al [18] investigated the greening strategies with cross-channel return service, and found that the retailer would cooperate with the manufacturer when the spillover effect was greater than a threshold by comparing results with those without cross-channel return service; Heydari et al [19] obtained the optimal decision on product greenness of the manufacturer, e-channel price of the distributor, and retail price of the retailer, and developed a coordinated decision model to enhance greenness and reduce price in both the e-channel and retail channel.…”
Section: A Product Greenness Of Supply Chainmentioning
confidence: 99%